Commentary: Government and Market Surveillance, Emergence of Mass Political Society, and the Need for Progressive Social Change - Grabiner, Gene (Social justice, 2012)
In this commentary, the author examines the political implications of the documents leaked by NSA whistleblower Edward Snowden. The essay examines the larger post-World War II intelligence framework that sought to ensure polarized centers of wealth and power, and it also draws lessons from the political reaction to the leaks in the United States, from Congress to the media to military leaders. Also covered are the dangers to democracy posed by the erosion of privacy rights by government spy agencies in conjunction with Internet companies whose profit margins depend on augmenting databases that contain the personal opinions and buying preferences of all who use these services. Finally, the author discusses the legislative and judicial limits to law enforcement searches and seizures of persons and property.